Biology and Role of Extracellular Vesicles (EVs) in the Pathogenesis of Thrombosis - Zarà, Marta (Int J Mol Sci, 2019)
Extracellular vesicles (EVs) are well-established mediators of cell-to-cell communication. EVs can be released by every cell type and they can be classified into three major groups according to their biogenesis, dimension, density, and predominant protein markers: exosomes, microvesicles, and apoptotic bodies. During their formation, EVs associate with specific cargo from their parental cell that can include RNAs, free fatty acids, surface receptors, and proteins. The biological function of EVs is to maintain cellular and tissue homeostasis by transferring critical biological cargos to distal or neighboring recipient cells. On the other hand, their role in intercellular communication may also contribute to the pathogenesis of several diseases, including thrombosis. More recently, their physiological and biochemical properties have suggested their use as a therapeutic tool in tissue regeneration as well as a novel option for drug delivery. In this review, we will summarize the impact of EVs released from blood and vascular cells in arterial and venous thrombosis, describing the mechanisms by which EVs affect thrombosis and their potential clinical applications.